Antihyperglycaemic and antiperoxidative effect of Helicteres igora L. bark extracts in streptozotocin-induced diabetic rats - Kumar, Ganesan; Banu, Gani Sharmila; Murugesan, Arunachalam Ganesan; Pandian, Moses Rajasekara (Journal of Applied Biomedicine, 2007)
The present investigation shows the antihyperglycaemic activity of aqueous extract of bark of Helicteres isora L. (100, 200mg/kg b.w/p.o) in streptozotocin (STZ) induced diabetic rats. Blood glucose levels, body weight, food and liquid intake were measured on every 5th day over a period of 14 days. A single injection of STZ at a dose of 60mg/kg b.w/i.p elevated the glucose levels >240mg/dl after 5 days. Administration of H.isora at a dose of 100, 200mg/kg/p.o resulted in a significant (p<0.05) reduction in blood glucose levels. Body weights were significantly (p<0.05) reduced in STZ-induced diabetic rats when compared to normal rats while the extract significantly (p<0.05) prevented a decrease in body weight in the H.isora treated animals. The study also evaluated the antioxidant potential of H.isora in STZ-induced diabetic rats. Decreased levels of thiobarbituric acid reactive substances (TBARS), increased levels of reduced glutathione (GSH) and the activities of superoxide dismutase (SOD) and catalase (CAT) resulted in the reduction of free radical formation in various tissues such as liver, kidney, and brain of the diabetic rats. Tolbutamide was used as a standard reference drug. The results clearly indicate that the aqueous extract of bark of Helicteres isora exhibits significant antihyperglycaemic and in vivo antioxidant activity in STZ-induced diabetic rats and the results were found to be dose dependent.
Keywords: streptozocin; Animals; experimentální diabetes mellitus; katalasa; Superoxide Dismutase; Malvaceae; Antioxidants; Plant Bark; Rats, Wistar; Catalase; slézovité; tolbutamid; superoxiddismutasa; kůra rostlin; rostlinné extrakty; Hypoglycemic Agents; Reactive Oxygen Species; peroxidace lipidů; hypoglykemika; Lipid Peroxidation; Tolbutamide; antioxidancia; Plant Extracts; reaktivní formy kyslíku; Streptozocin; zvířata; potkani Wistar; Diabetes Mellitus, Experimental